Chronic constrictive pericarditis complicated with huge right atrial thrombus in a child with abdominal tuberculosis: a rare life-threatening condition. Issue 11 (6th November 2019) - Kumar, Rupesh; Raja, Javid; Rawat, Sanjib; Srivastava, Ayush; Thingnam, Shyam Kumar Singh
Abstract: Chronic constrictive pericarditis (CCP) is the most common pericardial pathology. CCP complicating with intracardiac thrombus is a rare entity, the detection of thrombus preoperatively is life-saving in avoiding the risk of pulmonary thromboembolism during anterior pericardiectomy. Transesophageal echocardiography has been shown to have better sensitivity in detecting atrial thrombus than transthoracic echocardiography. Surgical removal of right atrial thrombus under cardiopulmonary bypass should be considered.